The effect of unloading and reloading on the compression behaviour of reconstituted clays - Habibbeygi, F.; Nikraz, Hamid (The Geomate International Society, 2018)
Oedometer tests were carried out on reconstituted clays to investigate the compressibility of soft clays with high initial water content under repetitive cycles of unloading/reloading. It is necessary to estimate the compression indices under repetitive loadings to predict the settlement of clayey layers. The results indicate that the unloading/reloading loop can be represented by a bi-linear line in a semi-logarithmic plane with three definite slopes (compression indices). Furthermore, the compression indices of unloading and reloading can be estimated using the compression and swell indices with reasonable accuracy. The reloading part can also be defined by two initial and final slopes. The difference in these two aforementioned slopes can be explained by the balance of physico-chemical and mechanical forces. When the consolidation stress is less than the remolded yield stress, the compression behavior is mainly controlled by the physicochemical effect. In fact, the change in the clay micro-structure is small; however, for stresses greater than remolded yield stress, the soil structure demolishes and the clay microstructure is completely affected. Consequently, the mechanical force controls the deformation which results in a sharp decrease in the void ratio.